2018
DOI: 10.3389/fphys.2018.00893
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Oxidative Stress and Inflammation to the Neurogenic Hypertension Induced by Intermittent Hypoxia

Abstract: Chronic intermittent hypoxia (CIH), the hallmark of obstructive sleep apnea, is the main risk factor to develop systemic hypertension. Oxidative stress, inflammation, and sympathetic overflow have been proposed as possible mechanisms underlying the CIH-induced hypertension. CIH potentiates the carotid body (CB) chemosensory discharge leading to sympathetic overflow, autonomic dysfunction, and hypertension. Oxidative stress and pro-inflammatory molecules are involved in neurogenic models of hypertension, acting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 79 publications
0
28
0
Order By: Relevance
“…There is a growing body of evidence suggesting that in addition to the neurotransmitters, immune signalling, as triggered by the activated innate immune system, can also modulate CB function (Fernandez et al., 2008; Kahlin et al., 2014; Lam et al., 2012; Liu, He, Stensaas, Dinger, & Fidone, 2009; Nardocci et al., 2015; Oyarce & Iturriaga, 2018). The initial immune response to various inflammogens, such as pathogen‐associated molecular patterns (PAMPs), results in mostly positive, regenerative effects; however, depending on the scale and duration of the inflammatory trigger, it may also develop into more detrimental hyperinflammatory conditions, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of evidence suggesting that in addition to the neurotransmitters, immune signalling, as triggered by the activated innate immune system, can also modulate CB function (Fernandez et al., 2008; Kahlin et al., 2014; Lam et al., 2012; Liu, He, Stensaas, Dinger, & Fidone, 2009; Nardocci et al., 2015; Oyarce & Iturriaga, 2018). The initial immune response to various inflammogens, such as pathogen‐associated molecular patterns (PAMPs), results in mostly positive, regenerative effects; however, depending on the scale and duration of the inflammatory trigger, it may also develop into more detrimental hyperinflammatory conditions, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Well‐matched control samples are even more rare. Another major hurdle in understanding H/I‐induced molecular cascades is the complex milieu of secondary inflammatory mediators and cellular debris that accompany cell death (Oyarce & Iturriaga, ). These confounding factors make it difficult to ascertain whether such molecular events are secondary to hypoxia, subsequent inflammation, or both.…”
Section: Introductionmentioning
confidence: 99%
“…This explains the enhanced sympathetic activity after glutamate injection in the cNTS in CIH-exposed rats compared with healthy rats (Costa-Silva et al, 2012). Other studies showed that exposure to CIH is associated with the upregulation of glutamatergic neurons in the NTS and increased expression of c-fos and fosB in the RVLM (Oyarce and Iturriaga, 2018). Therefore, increased peripheral afferent activity causes exaggerated central neural activity, which increases the production of ROS and cytokines in the NTS.…”
Section: Mechanisms Of Cih-induced Hypertensionmentioning
confidence: 98%
“…This induces microglial activation, which stimulates further increases in the levels of inflammatory cytokines. Exposure to CIH for 21 days caused an elevation of pro-inflammatory cytokines in the NTS and RVLM (Oyarce and Iturriaga, 2018). This hyperactivates NTS and PVN neurons, which increases renal sympathetic nerve activity and Ang II secretion.…”
Section: Mechanisms Of Cih-induced Hypertensionmentioning
confidence: 99%